Evaluation of Different Approaches for Sinus Membrane Perforation Repair During Sinus Elevation: A Systematic Review and Meta-analysis - Soares, Lelio Fernando Ferreira [UNESP]; Almeida Malzoni, Carolina Mendonca de [UNESP]; Silveira, Marcela lunes da; Marcantonio Jr, Elcio [UNESP]; Pigossi, Suzane Cristina (Quintessence Publishing Co Inc, 2024)
Purpose: To evaluate the Impact of different approaches to sinus membrane perforation (SMP) repair on bone formation, postoperative complications, and implant loss risk. Materialsand Methods: Electronic searches on Pub Med, Web of Science, Scopus, Embase, and Cochrane Library databases were conducted for publications up to February 2021. All included articles reported SMPs submitted for repair. The proportion of implant loss in repaired SMP sites was calculated using a random-effects model meta-analysis. Results: A total of 130 studies reporting SMP repair protocols were included in the systematic review, with 20 selected for meta-analysis. A total of 1,972 sinuses that were perforated and repaired during sinus elevation using different approaches were included in the qualitative analysis. The resorbable collagen membrane was the most commonly reported treatment. The presence of sinusitis was the most frequently described complication. Regarding bone parameters, the majority of studies described no differences between perforated and repaired sinuses and intact membranes. No difference in the implant loss proportion was observed between sites with repaired SMP compared to undetected SMP. The proportion of implant loss in repaired sinuses membrane sites (independent of the material or implant placement time) was 4% (95% CI: 2.0 to 8.0). In meta-regression analysis, no association was observed between the SMP size and implant loss proportion (P= .86). Conclusions: The materials and techniques indicated for SMP management seem to securely seal the maxillary sinus, without a negative effect on the ultimate survival of the implants placed in the affected sinuses. Int. Oral Maxillofac lmplants 2024;39:107-118. doi: 10.11607/jomi.10180
Keywords: sinus elevation; sinus membrane perforation; sinus membrane repair